Contemporary aspects on the immunopathogenesis of skin lesions in canine leishmaniosis (Leishmania infantum) - PAPADOGIANNAKIS (E. Ι. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ), E. I.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; KOUTINAS (X.Κ. ΚΟΥΤΙΝΑΣ), C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Dog's immunologic reaction to Leishmania infantum inoculation may determine not only the diversity of the observed skin lesions but also the susceptibility or resistance of the dog to develop the disease.The expression of costimulatory molecules, such as B7, by infected macrophages along with the action of cytokines IL-12 and IFN-γ, results in Thl CD4+ cell activation and their infiltration of the dermis. The latter, in turn, activate macrophages to kill the parasite. Failure of the infected macrophages to express these molecules, results in dermis infiltration with Th2 CD4+ cells and macrophage in activation which facilitates the spreading of parasites and thus the perpetuation of the infection. The normal function of Thl CD4+ cells depends, at least partially, on FasL expression. In the exfoliative dermatitis of canine leishmaniosis the immune response is more efficient than in dermal nodules while in the ulcerative dermatitis a mixed type of immune response occurs. In the exfoliative dermatitis, Τ cells predominate in the inflammatory infiltrate while granulomatous sebaceous adenitis is a common histopathological finding. CD4+:CD8+ ratio is approximately 1 and in both immunocytes half of them are memory cells. Extrapolating from immunopathology, the use of canine CD28 molecule along with that of IL-12 and IFN-γ, may be quite useful in both the antileishmanial treatment and the preparation of an effective vaccine.